Penjualan Tuak di Paciran Lamongan Perspektif Hukum Pidana Islam - Musyafaah, Nur Lailatul; Faiza, Nabilatul (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
The article discusses the sale of tuak drinks in Paciran Lamongan from Islamic criminal law's perspective. This research is field research. Data comes from observations, interviews, and documentation. Data will be analyzed using a descriptive qualitative method with a deductive mindset. Based on laboratory test results on 800ml of tuak drink, it contains alcohol of 8.5%. Based on Islamic law, it considered as khamr. The Regional Regulation of Lamongan Regency, Number 03 of 2004 concerning Supervision and Control of the Distribution of Liquor, alcohol of 8.5% categorized as level B liquor and it's distribution is prohibited. Those who violate the rule, punishable with imprisonment for a maximum of 3 months or a maximum fine of Rp. 50,000,000- (fifty million rupiah). According to Islamic law’s perspective, the penalty given to the seller of liquor is ?add's penalty of 40 to 80 whips. In case of the punishment of ?add cannot be carried out, the criminal can be punished by ta'z?r referring to the applicable laws or regulations.